2009
DOI: 10.1016/j.aca.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of selenium by atomic fluorescence and sulfur by molecular emission by flow-injection hydride generation with on-line reduction for the determination of selenate, sulfate and sulfite

Abstract: Simultaneous detection of selenium by atomic fluorescence and sulfur by molecular emission by flowinjection hydride generation with on-line reduction for the determination of selenate, sulfate and sulfite" (2009 An inductively coupled plasma atomic fluorescence spectrometry (ICP-AFS) instrument, was modified so that it was capable of monitoring transient chromatographic or flow-injection profiles and that sulfur molecular emission and selenium atomic fluorescence could be monitored simultaneously in an argon-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The cell uses a graphite tube cathode and a reticulate Pt wire anode without an ion-exchange membrane and an individual anolyte; a limit of detection for As of 0 ng mL -1 could be obtained, and real samples were analyzed (54). Also multielement determinations could be realized, as shown at the hand of the simultaneous detection of Se by atomic fluorescence and S by molecular emission by flow injection hydride generation with online reduction for the determination of selenate, sulfate, and sulfite (55). Apart from volatile species generation, also, electrothermal vaporization could be used for forming the atom vapor, as shown by the determination of Cd in rice and water by tungsten coil electrothermal vaporization-atomic fluorescence spectrometry after cloud point extraction (56).…”
Section: Atomic Fluorescence Spectrometrymentioning
confidence: 99%
“…The cell uses a graphite tube cathode and a reticulate Pt wire anode without an ion-exchange membrane and an individual anolyte; a limit of detection for As of 0 ng mL -1 could be obtained, and real samples were analyzed (54). Also multielement determinations could be realized, as shown at the hand of the simultaneous detection of Se by atomic fluorescence and S by molecular emission by flow injection hydride generation with online reduction for the determination of selenate, sulfate, and sulfite (55). Apart from volatile species generation, also, electrothermal vaporization could be used for forming the atom vapor, as shown by the determination of Cd in rice and water by tungsten coil electrothermal vaporization-atomic fluorescence spectrometry after cloud point extraction (56).…”
Section: Atomic Fluorescence Spectrometrymentioning
confidence: 99%
“…However, CVG-AFS is mainly applied for single-element measurements. A literature survey revealed that most of such work concentrated on singleelement analysis, whereas, to the best of our knowledge, no CVG-AFS procedure for the simultaneous determination of As and Hg in human hair, nails, and saliva has been published previously (19)(20)(21)(22)(23)(24)(25)(26)(27). internal organs.…”
Section: Introductionmentioning
confidence: 99%
“…To improve selectivity and accuracy, CVG gas phase molecular fluorescence spectrometry (GP-MFS) was developed to reliably quantify SO 2 via the detection of its molecular fluorescence with a commercial atomic fluorescence spectrometer equipped with a zinc hollow cathode lamp (Zn HCL). , The CVG-GP-MFS was further successfully employed for the selective and sensitive detection of sulfide after its oxidation to SO 2 by miniature point discharge (μPD) . Unfortunately, several serious impediments still remain to the further evolution of CVG-GP-MFS coupling with μPD-assisted oxidation.…”
mentioning
confidence: 99%